OPTICAL PROPERTIES MODULATION OF CYANINE DYES IN ORGANIC SOLVENTS AND IN THE CRITICAL INTRACELLULAR pH WINDOW - SISA, Richard; BRÉM, Balázs; GÁL, Emese; GĂINĂ, Luiza; PORUMB, Dan Ioan; CRISTEA, Castelia; SILAGHI-DUMITRESCU, Luminita (Studia Universitatis Babeș-Bolyai Chemia, 2019)
The synthesis of new 2-(2-(3-formyl-10H-phenothiazin-7yl)vinyl)-3H-indolium iodide and comparison of the UV–visible absorption/emission spectral changes for several indolium cyanine dyes upon variation of organic solvents and aqueous solutions with pH in the range between 5–8 pH units were described.